Evaluation of probiotic potential of lactic acid bacteria to reduce in vitro cholesterol - Cueto, Clementina (2012)
Daily consumption of probiotics reduce levels of serum cholesterol by up to 3%, which is significant to prevent hypercholesterolemia, a risk factor for cardiovascular disease and cause of mortality. The genus Lactobacillus is used in industry as a probiotic and some species reduce serum cholesterol by two mechanisms, the adsorption of cholesterol and the production of the enzyme bile salt hydrolase, which vary according to species. The aim of the study was to assess the ability of probiotic bacteria group isolated from coast serum. 53 strains were isolated from nine coastal serum sample; the sensitivity to cefoxitin and vancomycin, and the tolerance to pH 2.0 and 0.3% bile salts were evaluated to determine its probiotic potential. Five microorganisms were selected and molecularly identified as Lactobacillus fermentum. The ability to absorb cholesterol measured by the method of Kimoto, showed a reduction of 53.06 ± 2.69 μg.mL-1 for strain K73 and 7.23 ± 2.69 μg. mL-1 for K75. These same strains showed the highest total and specific activity of the enzyme. The results didn´t show a relationship between the production of enzyme and adsorption of cholesterol. The strain with the greatest probiotic potential was K73. This hypocholesterolemic property will give strains added value to start the search for food matrices that allow decreasing serum cholesterol levels.